PERAN VISUAL EVOKED POTENTIAL PADA PASIEN DIABETES MELITUS TIPE2 DENGAN DAN TANPA RETINOPATI DIABETIK - Bill Jones Tanawal,* Melke Joanne Tumboimbela,** Corry Novita Mahama** (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION DIABETIC RETINOPATHY DR IS A COMMON COMPLICATION OF TYPE2 DIABETES MELLITUS T2DM MINIMAL FUNCTIONAL CHANGE OF NEURAL LAYERS OF THE RETINA OCCURS BEFORE STRUCTURAL CHANGES THUS UNDETECTED BY FUNDUSCOPY THIS DAMAGE COULD BE IDENTIFIED EARLIER BY P100 LATENCY CHANGES IN VISUAL EVOKED POTENTIAL VEP